2015
DOI: 10.1016/j.foodchem.2014.10.135
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal properties and inhibitory effects upon aflatoxin production of Thymus vulgaris L. by Aspergillus flavus Link

Abstract: The antifungal and antiaflatoxigenic properties of Thymus vulgaris essential oil (TEO) were evaluated upon Aspergillus flavus "in vitro". Suspension containing 10(6) of A. flavus were cultivated with TEO in concentrations ranging from 50 to 500 μg/mL. TEO reached minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) at 250 μg/mL. Inhibition of ergosterol biosynthesis was detected at a concentration of 100 μg/mL of TEO. Morphological evaluation performed by both light microscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 24 publications
9
39
0
3
Order By: Relevance
“…In addition, Kohiyama et al. reported that T. vulgaris EO (40.6% borneol, 19.9% α‐terpineol) inhibited A. flavus growth (MIC=250 μg/ml) and aflatoxin production . With respect to T. vulgaris EO (density=0.92 g/ml, at 20°C), we found a MIC value close to that reported by Kohiyama et al.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, Kohiyama et al. reported that T. vulgaris EO (40.6% borneol, 19.9% α‐terpineol) inhibited A. flavus growth (MIC=250 μg/ml) and aflatoxin production . With respect to T. vulgaris EO (density=0.92 g/ml, at 20°C), we found a MIC value close to that reported by Kohiyama et al.…”
Section: Resultssupporting
confidence: 87%
“…34 Antioxidant aromatic compounds such as thymol and p-cymene were detected in higher levels in T. citriodorus 'Aureus' EO than in T. aflatoxin production. 36 With respect to T. vulgaris EO (density=0.92 g/ml, at 20°C), we found a MIC value close to that reported by (Table 3). (Figure 1, Figure 2 μM of thymol produced DNA damaging effects.…”
Section: Antioxidant Activitysupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, histological analysis of liver from chickens fed with plant compounds revealed significantly lesser hepatocellular degeneration, inflammation and necrosis as compared to control birds [175]. Similar inhibitory effect on aflatoxins production was obtained with other plant-derived antimicrobials, namely Thymus eriocalyx [176], Thymus vulgaris [177], thyme , anise , cinnamon , and spearmint [178]. These results suggest that plant compounds could be used as feed/food additives to control aflatoxins contamination in food products or animal feed.…”
Section: Studies Highlighting the Anti-toxin Properties Of Plant-dmentioning
confidence: 85%
“…As plants grow, they produce many metabolites that serve as a defense against a number of environmental stresses. Therefore, plant extracts have long been studied as protective bioactive agents and it was demonstrated that some of them have antifungal or anti-toxinogenic properties [19,20]. …”
Section: Introductionmentioning
confidence: 99%